Phytoseiid mites (Acari: Mesostigmata) from Araucaria Forest of the State of Rio Grande do Sul, Brazil, with new records and descriptions of four new species - Gonçalves, Dinarte; Cunha, Uemerson Silva Da; Bampi, Paula Maria; Moraes, Gilberto José De; Ferla, Noeli Juarez (Zootaxa, 2015)
This paper reports on the Phytoseiidae from an Araucaria forest in the State of Rio Grande do Sul, describing four new species, namely Transeius kroeffis n. sp., Typhlodromalus araucariae n. sp., Typhlodromips pompeui n. sp. and Typhlodromips salvadorii n. sp.. Iphiseiodes moraesi Ferla & Silva, Neoseiulus tunus (DeLeon), Typhlodromips japi Lofego, Demite & Feres, Typhlodromips pallinii Gonçalves, Silva & Ferla, Typhloseiopsis dorsoreticulatus Lofego, Demite & Feres are reported for the first time from this type of habitat in Rio Grande do Sul state, Brazil.